Campus Introduction Socialization In The World Of Education In The 21st Century Battuta University - Panggabean, Dewi Sartika; Misykah, Zulvia; Wahyuni, Nur (Outline Publisher, 2024)
Campus introduction plays an important role in helping new students adapt to the university environment in the 21st century era. Discussing changes in educational paradigms, the influence of globalization, and the impact of technology on the teaching and learning process. Campus socialization is a key strategy in supporting student development and success amidst ever-developing social, economic and technological dynamics. The educational paradigm that shifts from the traditional model to a focus on 21st century skills is the basis for changes in the campus induction process. Globalization introduces competition in the job market, driving the need for global skills in students. Technological advances change the way of learning, so that campus outreach includes the introduction of educational technology and the use of digital tools. Campus outreach not only provides academic information, but also emphasizes student life balance, supports mental well-being, and introduces cultural values. Students are directed to seek more active and involved experiences in their educational environment, with campus socialization providing opportunities to engage in social, academic and self-development activities. An effective strategy for implementing the Introduction to New Student Campus Life (PKKMB) in the 21st century, highlighting important aspects such as introducing cultural values, fostering awareness of defending the country, preventing intolerance, and preparing students to face the industrial revolution 4.0. Through a mature approach, PKKMB is expected to provide initial provisions so that students become individuals who have depth of knowledge, nobility of morals, love of the country, and global competitiveness. The case study at Battuta University illustrates successful implementation involving all elements of the campus and provides concrete views regarding the success and impact of PKKMB.